O princípio da dignidade humana: mulheres idosas em estado de encarceramento - Eduardo, Carlos Henrique (Universidade Federal de São Carlos, 2024)
Human dignity must be achieved in all spheres of society. In the case of incarcerated individuals, it is known that prisons are mostly built to house the male population. However, there is a growing number of women sentenced to prison terms, individuals with intrinsic needs in relation to their gender who, in this reality, may not have their principles of dignity respected. With the aging of the Brazilian population, it is plausible to infer that a greater number of elderly women, aged 60 or over, live in a state of incarceration, facing the prison system with the intersectionality between gender and age issues. In this context, the objective of this research is to discuss the principle of human dignity of elderly women in a state of incarceration. To achieve this objective, a concatenation of a Literature Review and interviews with two former inmates, workers at Espaço Memória Carandiru, was carried out. The theoretical basis was conducted with primary source materials, in Portuguese, published between 2016 and 2022, on the Scientific Electronic Library Online (SciELO), Brazilian Digital Library of Theses and Dissertations (BDTD) and Google Scholar platforms, using the descriptors: dignity; incarceration; women; elderly; and visits. Six publications were selected, in addition to the books Encarceradas, by Dráuzio Varella, and Condições de saúde e qualidade de vida dos presos idoso do Estado do Rio de Janeiro, by Maria Cecília Minayo and Patrícia Constantino. The real gap in the scientific literature on the topic of abandonment of elderly incarcerated women is highlighted, the result of a historical erasure by a sexist, androcentric and white society inherited from European colonization, which punishes and makes this portion of the population invisible, the precarious state in which they live and keeps them on the margins of collective belonging, in perpetual marginalization and social exclusion, the result of stigmas and prejudices. The historical erasure of elderly women in prison and the consequent violation of human rights also involves the idea of ​​breaking the imaginary of old age as synonymous with fragility, passivity and kindness, the socio-affective abandonment of these women by their spouses and family members, the lack of practical public policies aimed at women in prisons or even the denial of debate by Public Security organizations on the subject, the necropolitics of the State and the failure of rehabilitation strategies for these women, in addition to the prison system itself that does not meet the physical, psychological and emotional needs of elderly women. Other problems that keep elderly women in prison in a state of vulnerability include the inadequacy of physical spaces, food, and health care. This panorama is also linked to the socioeconomic conditions of incarcerated women, the majority of whom are poor, black or brown, and have little education. Thus, despite national regulatory efforts to try to expand initiatives that address the conditions of incarcerated women, necropolitics and ageism remain, and, ultimately, the lack of visits to these women demonstrates the culminating abandonment of the reality they live in today's society.
The principle of human dignity: elderly women in prison
Keywords: envelhecer na prisão; gênero e etarismo no sistema prisional; condições humanas de idosas encarceradas; necropolítica; aging in prison; gender and ageism in the prison system; Human conditions of elderly women in prison; necropolitics; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO::DIREITO CONSTITUCIONAL; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO::DIREITO PENAL; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO::DIREITO PROCESSUAL PENAL